Characterization of Energy Portability Tools to Implement in Colombia - Mendoza-Becerra, Martha-Eliana; Ordoñez-Eraso, Hugo-Armando; Niño-Zambrano, Miguel-Ángel; Cobos-Lozada, Carlos-Alberto; García-Sierra, Rodolfo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Electricity is one of the fundamental components that drive the economy, i. e. the higher the economic growth, the higher the energy consumption and vice versa. Therefore, the energy market must be able to cover the increase in energy demand and establish strategies for efficient energy use. In the United Kingdom, the implementation of modern technologies in the electric system has been boosted with an automatic energy supplier switching process known as auto-switching. In this strategy, users are not exclusively bound to the local supplier and have the freedom to switch. On the other hand, Colombia could liberalize the energy market through an auto-switching pilot program to increase competition among energy suppliers by deregulating the tariffs. This would facilitate the supplier selection process for new clients by allowing them to choose the supplier with the lowest rate, best quality, and desired energy source, among others. This paper presents a characterization of the attributes and functionalities of the main auto-switching tools in the United Kingdom. Additionally, it proposes an adapted auto-switching tool for the Colombian energy market considering information from Enel Codensa related to the registration of new potential customers, affiliation with energy suppliers, offers views, and notifications for customers, among others. To liberalize the Colombian energy market, it is necessary to promote these types of tools that provide greater benefits to users and suppliers.